FAMILY BURDEN AND STRESS AMONG CAREGIVER OF ORAL CANCER PATIENTS AT KRISHNA HOSPITAL KARAD - Hiremath, Prabhuswami; Mohite, Vaishali R; Naregal, Prakash; Chendake, Mahesh; Mulani, Afsana; More, Ujwala R (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: Cancer is a major life-threatening disease and has its impact on both patients and their family members. Caregivers also play the very important role in the care of the patients with cancer. (1) Asses the burden among caregivers of patients with oral cancer using burden inventory. (2) Assess the perceived stress among caregivers of patients with oral cancer using Perceived Stress Scale (PSS). (3) Identify the correlation between burden and perceived stress with selected sociodemographic variable. There is mounting evidence that during advanced stages of illness, changes in family roles, and the burden placed on family caregivers may negatively affect quality of life for cancer patients, as well as their caregivers. Attending to the needs of the families of patients not only will benefit family members but also may help patients with their own emotional responses and management of their disease. The study objectives were to asses the burden and the perceived stress among caregivers of patients with oral cancer patients. Methods: Quantitative nonexperimental approach with descriptive survey design was selected for study. 40 caregivers of patients with oral cancer were selected through convenience sampling technique. The study included the caregivers of 21-50 years age group who is providing care patients with oral cancers, who are responding and interested to participate, and available at the time of the study. Caregiver's burden was assessed using caregiver burden scale. A stress of the caregiver was assessed by the PSS. Results: Demographic variable shows that maximum sample belongs 40-50 (40%) years of age group, male gender (65%), married (90%), nuclear family (65%), house wife by occupation (60%), spouse to the patients (45%), below graduated education (72%), 6 months to 1 year in providing care (47%), having health benefit from government (52%), and accompanying patient regularly to the hospital (72%). In this study, 3 (7.5%) caregiver were said that no burden, 13 (32.5%) samples shown mild burden, 15 (37.5%) relative indicated moderate burden, and 9 (22.5%) samples shown severe burden; 4 (10%) samples shown low stress, 22 (55%) caregiver presented moderate stress, and 14 (35%) samples had high stress. Conclusion: Caregivers are often patients' primary source of support, many experience significant burden, particularly with respect to their physical and psychological well-being, economic circumstances, and social and personal relationships. Keywords: Family, Burden, Stress, Caregiver, Oral cancer.